Visual and Structural Packaging Cues and their Effects on Consumer Buying Decisions: A Quantitative Study in Selected Philippine Municipalities - Claudel, Herzyl Jay B.; Villasan, Virnard B.; Alonzo, Albert A.; Suazo, Maria Leah E.; Vicente, Oliver Danil J. (International Review of Management and Marketing, 2026)
This study investigates the influence of primary packaging elements, design, size, shape, and color, on consumer buying decisions, framed within Kano’s Theory of Attractive Quality. Kano’s framework differentiates product features into must-be, one-dimensional, and attractive qualities, providing insight into how packaging attributes differentially impact consumer satisfaction and purchase behavior. A quantitative, descriptive-correlational research design was employed to examine these relationships among 300 consumers aged 18 and above in Manticao, Lugait, and Naawan, Misamis Oriental, Philippines. Purposive sampling ensured respondents had relevant experience with packaged products. Data were collected via a structured online questionnaire adapted from validated instruments, using a five-point Likert scale, and underwent expert review and pilot testing to ensure validity and reliability. Descriptive statistics profiled respondents’ perceptions, while multiple regression analysis assessed the direction and strength of relationships between packaging elements and buying decisions. Findings indicate that packaging design exerts a positive but non-significant effect, functioning as a must-be quality that prevents dissatisfaction without directly driving purchases. Packaging size and shape significantly influence buying decisions, aligning with one-dimensional qualities where functional performance directly enhances satisfaction. Packaging color emerged as the strongest predictor, representing an attractive quality that delights consumers and strongly motivates purchase behavior. These results highlight that strategic management of packaging attributes can enhance consumer satisfaction, brand appeal, and purchase likelihood. The study underscores the dual functional and sensory role of packaging in marketing, with practical implications for product development and brand strategy. By integrating Kano’s theoretical perspective with empirical evidence from a Philippine context, this research contributes to the understanding of how primary packaging elements shape consumer behavior in low-involvement products.